2017
DOI: 10.1002/jnr.24065
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion MRI and the detection of alterations following traumatic brain injury

Abstract: This article provides a review of brain tissue alterations that may be detectable using diffusion MRI (dMRI) approaches and an overview and perspective on the modern dMRI toolkits for characterizing alterations that follow traumatic brain injury (TBI). Non-invasive imaging is a cornerstone of clinical treatment of TBI and has become increasingly used for pre-clinical and basic research studies. In particular, quantitative MRI methods have the potential to distinguish and evaluate the complex collection of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 104 publications
6
83
1
Order By: Relevance
“…In our experiments, we observed that data corrected only for motion and eddy‐current distortion, but not for EPI distortions, as typically done in major studies, have a median variability higher by 32% for Trace, 15% for FA, and 34% for the primary eigenvector, compared to the EPI corrected data. These findings underscore the importance of including EPI distortion correction to increase the power of diffusion MRI studies, in particular when seeking subtle biological changes, for example those due to mild traumatic brain injury 40,41 …”
Section: Discussionmentioning
confidence: 90%
“…In our experiments, we observed that data corrected only for motion and eddy‐current distortion, but not for EPI distortions, as typically done in major studies, have a median variability higher by 32% for Trace, 15% for FA, and 34% for the primary eigenvector, compared to the EPI corrected data. These findings underscore the importance of including EPI distortion correction to increase the power of diffusion MRI studies, in particular when seeking subtle biological changes, for example those due to mild traumatic brain injury 40,41 …”
Section: Discussionmentioning
confidence: 90%
“…This process initiates a cascade of ionic dysregulation and neuroinflammatory processes. Findings of decreased mean diffusivity are likely reflective of cytotoxic edema and inflammation in the acute phase following injury, with a decrease in axial diffusivity likely reflecting axonal damage resulting from cytoskeletal stretching (Hutchinson, Schwerin, Avram, Juliano, & Pierpaoli, 2017) and/or an increase in glial and Schwann cells in the extraaxonal space restricting diffusion parallel to axons (Beaulieu, 2002; Blumbergs et al, 1994; Hutchinson, Avram, et al, 2017; Pasternak et al, 2014). On the other hand, intracellular swelling results in decreased extracellular space within an axon and thus decreased ability for water to permeate through; as such, decreased radial diffusion would be expected.…”
Section: Discussionmentioning
confidence: 99%
“…To consistently select histologic sections from a similar location relative to the CCI lesion, ex vivo MRI scans were performed prior to sectioning, and regions of abnormal diffusion tensor imaging (DTI) values were identified according to previously described imaging findings along with details of image acquisition and processing (Hutchinson et al, 2016;Hutchinson, Schwerin, Avram, Juliano, & Pierpaoli, 2018 …”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%